Hubungan Antara Kestabilan Emosi Dengan Pembelian Impulsif Pada Mahasiswi - Octaviana, Ayun, Dra. Partini, M.Si (2017)
The purpose of this study was to to determine the relationship between the stability of emotions with Impulsive Purchases at the Faculty of Psychology student of Muhammadiyah University of Surakarta. The hypothesis is a negative correlation between the stability of emotions with Impulsive Purchases at the Faculty of Psychology student of Muhammadiyah University of Surakarta. Subjects in this study were 120 subjects. The population used in this study is a student at the Faculty of Psychology 2013,2014,2015,2016 force. The measuring instruments used in this study are: a) Scale Stability Emotion and b) Purchase Impulsive Scale. Data analysis techniques used in this study is the product moment correlation. Conclusion hypothesis no correlation between Emotional Stability with Impulsive Purchases at the Faculty of Psychology student of Muhammadiyah University of Surakarta. This is indicated by the value of r = -0.042 with sig. 0.324; (P> 0.05), which means that the hypothesis proposed by the researchers rejected. The level of emotional stability is high while the level of Impulsive Purchases moderate. This is indicated by the empirical mean (RE) Emotional Stability at 87.47 and the mean hypothetical (RH) of 75, while the average empirical (RE) Impulsive Purchases amounted to 61.78 and the mean hypothetical (RH) of 70. Effective contribution (SE) Emotional Maturity 0.17%. It is still 99.83% are other variables that can affect the stability of the variables outside Impulsive Purchases Emotions, for example Peers